Constraints of Linkages Among University Research-Extension andFarmers in India and Ethiopia : A Critical Analysis - K.S., Helen.; Singh, Premlata; K, Vijayaragvan. (Indian Journal of Extension Education, 2010)
The present study focused on effectiveness of agricultural research-extension and farmer linkage in agricultural universities in India and Ehiopia. A total of 84 agriculture scientists of Punjab Agricultural University in India and 87 agricultural scientists of Hawassa University in Ethiopia constituted the sample in case of agricultural scientists, and 44 farmers from India and 34 farmers from Ethiopia constituted the total sample for farmers. Data were collected through especially designed interview schedule developed for the study. The major constraints for linkage among scientists and farmers in India were lack of proper policy, lack of funds and administrative problems (44.05%) and poor transportation facilities (41.67%). In case of Ethiopia, the major constraints were poor transportation facilities (19.54%) and workload of scientists (19.54%). The major constraints for linkage among extension workers and farmers in India were poor transportation facilities' (17.85%) and lack of finance/budget/funds (15.47%). In case of Ethiopia, the major constraints were inefficient and poor quality technology (27.58%) and lack of infrastructure (10.34%). As regards sources of information, the farmers received maximum farm information from friends and neighbours. In case of India (84.09%) and Ethiopia (82.35%), only a small proportion (13.63%) farmers in India participated in the research projects conducted by the agricultural universities while the corresponding figure in case of Ethiopia was only 5.88 per cent. Adoption of modem technologies developed by the agricultural universities was found in the case of 65 per cent of the Indian farmers and 25.53 per cent Ethiopian farmers. In India (53.33%) and Ethiopia (61.53%), farmers reported not being aware of technology as a reason for non adoption.